1962
DOI: 10.1677/joe.0.0240453
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Cadmium Damage and Repair in Rat Testes and the Effects on the Pituitary Gonadotrophs

Abstract: Cadmium chloride, in a single subcutaneous injection, can destroy spermatogenic and interstitial cells in the rat testis (Pa\l =r%v\\l =i ' \zek,1957) and produce changes in the pituitary. The interstitial tissue is restored by ingrowths from the tunica and full androgen secretion returns before there is any regeneration of germinal epithelium.A cytological study has been made of the peripheral and central pituitary gonadotrophs; the latter revert almost to normal as the interstitial tissue regenerates, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

1964
1964
1975
1975

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…selective destructive effect of cadmium on the testis of the rat and mouse have since been confirmed by Meek (1959), Kar & Das (1960), Gunn, Gould & Anderson (1961), Allanson & Deanesly (1962), Chiquoine (1964), Mason, Brown, Young & Nesbit (1964) and others. During studies on the induction of interstitial cell tumours of the testis by cadmium (Gunn, Gould & Anderson, 1963), we noted that cadmium failed to cause any degree of damage to the testis of the BALB/c mouse.…”
mentioning
confidence: 80%
“…selective destructive effect of cadmium on the testis of the rat and mouse have since been confirmed by Meek (1959), Kar & Das (1960), Gunn, Gould & Anderson (1961), Allanson & Deanesly (1962), Chiquoine (1964), Mason, Brown, Young & Nesbit (1964) and others. During studies on the induction of interstitial cell tumours of the testis by cadmium (Gunn, Gould & Anderson, 1963), we noted that cadmium failed to cause any degree of damage to the testis of the BALB/c mouse.…”
mentioning
confidence: 80%
“…Changes in the gonadotrophic cells of the adenohypophysis, have been described as a result of 'cadmium castration' (Allanson & Deanesly, 1962;Girod, 1964;David & Ramaswami, 1971 …”
Section: Decidua and Placentaementioning
confidence: 99%
“…Gunn, Gould & Anderson (1963 a) showed that, after cadmium administration, avascular necrosis occurs in the testis, and they suggested that the necrosis may be due to interference with some enzymic system, possibly cadmium-zinc dependent, which controls the permeability of the endothelium in this vascular area. After cadmium damage, Leydig cell regeneration from the tunica albugínea has been described (Parizek, 1960;Allanson & Deanesly, 1962) and neoplasia of the regenerated Leydig cells has been observed (Gunn, Gould & Anderson, 1963&;Roe, Dukes, Cameron, Pugh & Mitchley, 1964). The present investigation deals with the biosynthesis in vitro of androst-4-ene-3, 17-dione (androstenedione) and testosterone from 3/?-hydroxypregn-5-en-20-one (pregnenolone) by testes and adrenals from rats up to 5 months after cadmium poisoning.…”
Section: Introductionmentioning
confidence: 99%